ANALISIS PENGARUH PENGAWASAN PIMPINAN DAN BUDAYA ORGANISASI TERHADAP DISIPLIN KERJA (Studi Pada Dinas Pemuda dan Olahraga Provinsi Jawa Tengah) - Khadijah, Intan; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2016)
The purpose of this research is to examine the effect of supervisory and organization culture toward work discipline. The research is investigated the work discipline of employees who work in the was conducted to Ministry of Youth and Sport, Central Java. The independent variables are supervisory and organization culture, and dependent variable is work discipline. The data were collected by using purposive sampling method. Direct questionnare use to obtain the data with 59 respondents from Ministry of Youth and Sport, Central Java employees. The data were analyzed with multiple linear reggresion method using SPSS (Statistical Product and Service Solution) 16. The research show that supervisory have a positive and significant influence on work discipline. Organization culture have a positive significant influence on work discipline. For the next research it’s recommended to add more variable and than to extend the population.